Distinct Expression Profiles for PTEN Transcript and Its Splice Variants in Cowden Syndrome and Bannayan-Riley-Ruvalcaba Syndrome - Sarquis, Marta S. (The American Society of Human Genetics, 2006)
Cowden syndrome (CS) and Bannayan-Riley-Ruvalcaba syndrome (BRRS) are autosomal dominant hamartoma syndromes. Germline PTEN mutations have been associated with 85% of CS cases and 65% of BRRS cases and also with other disorders, which are collectively referred to as the “PTEN hamartoma tumor syndrome.” The human PTEN gene has been previously found to express two naturally occurring splice variants (SVs). Recently, we identified eight novel naturally occurring PTEN SVs that result in different downstream signaling effects: SV3a, SV3b, SV3c (inclusion of various lengths of intron 3 3′ of exon 3), SV5a, SV5b, SV5c, SV5d (inclusion of various lengths of intron 5 3′ of exon 5), and SVΔEx6 (deletion of exon 6). We therefore sought to characterize the relative expression of 5′, middle, and 3′ full-length PTEN mRNA (FL-PTEN) and also of these eight PTEN SVs in 85 (65 female and 20 male) patients with CS/BRRS (with or without PTEN mutations) compared with 27 controls, using a SYBR green quantitative polymerase chain reaction method. Significantly reduced FL-PTEN levels were found in the probands, compared with those of controls (P<.01). Apart from FL-PTEN, SV3a is the most consistently relatively underexpressed in patients compared with controls. The patients showed relative underexpression of SV3a and SV3b and overexpression of SV5b (P=.005, P=.02, and P=.04, respectively). Indeed, there appears to be an SV expressional genotype-phenotype correlation in which the SV expressional profiles are distinct among CS, CS-like, and BRRS. The reduced FL-PTEN transcript expression, associated with differential expression of PTEN SVs, regardless of PTEN mutation status, supports the concept that modulation of PTEN inactivation may also occur at the transcription level influencing the specific phenotypes seen in these syndromes.